Periapical lesions in patients with primary Sjögren syndrome: A cross-sectional retrospective study of medical charts platform - Ilan Rotstein; Joseph Katz (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to assess the prevalence of acute periapical lesions in patients with pSS. Methods: Integrated data of hospital patients was used. Data from the corresponding diagnosis codes for pSS and acute periapical abscess was retrieved by searching the appropriate query in the database. The patient population analyzed was mixed, presenting with different disease conditions including periapical abscesses without sinus. The different diagnoses were coded using the international coding systems ICD 10. Diagnosis was made by calibrated dentists in a hospital setting based on clinical examination and imaging data. Patients with ICD 10 diagnosis code of acute periapical abscess were recorded and the prevalence of acute periapical abscesses in patients with primary Sjögren syndrome were compared to the prevalence in the total hospital patient population. The odds ratio (OR) for the prevalence of acute periapical abscesses and its association with pSS were calculated with a 95% confidence interval and the statistical difference between the groups was assessed. Results: The odds ratio (OR) for the prevalence of acute apical abscesses and its association with pSS were calculated and analyzed statistically. The prevalence of periapical abscesses in patients with pSS was 1.87% as compared to 0.58% in the general patient population of the hospital. The OR was 3.11 and the difference was statistically significant (p<0.0001). Conclusions: Under the conditions of this study, it appears that the prevalence of acute periapical abscesses is significantly higher in patients with pSS.